EXPLORING STAKEHOLDERS’ PERSPECTIVES ON INTRODUCING AN OLYMPIC EDUCATION PROGRAMME IN LEBANESE SCHOOLS TO PROMOTE SOCIAL COHESION - Abou Chabake, Chloé (Πανεπιστήμιο Πελοποννήσου, 2024)
Lebanon faces many challenges due to its religious diversity and cultural divisions; hence, fostering social cohesion is an essential concern. Starting at a young age and shaping future generations’ values and attitudes can potentially promote social cohesion and peaceful coexistence. This study explores stakeholders’ perspectives on introducing an Olympic education programme in Lebanese schools to promote social cohesion. This qualitative research will address the main research question on how implementing an Olympic education programme into the Lebanese school system can promote social cohesion among students. One-on-one semi-structured interviews with four key stakeholders from the sports and education fields will be done for a deep examination of the possible advantages and challenges of implementing such a programme into the current curriculum. The findings highlight the importance of addressing barriers to foster social cohesion. The benefits of Olympic education such as mutual understanding and respect present potential for fostering social cohesion. In addition, the socio-religious nature of the Lebanese society underlines the necessity of a careful cultural adaptation of the programme for a successful implementation. Finally, the recommendations suggest the collaboration of experts in Olympic education, multidisciplinary stakeholders and religious leaders for the creation of an Olympic education programme culturally adapted to Lebanese social diversity. Starting at a young age and increasing awareness through media channels are also among the recommendations. Most importantly, and for positive results, it is essential to have long-term commitment and consistent efforts.
Keywords: Φυσική αγωγή και εκπαίδευση - Μελέτη και διδασκαλία - Λίβανος; Ολυμπιακή παιδεία - Πρόγραμμα μαθημάτων - Λίβανος; Ολυμπιακή παιδεία - Μελέτη και διδασκαλία - Λίβανος; Φυσική αγωγή και εκπαίδευση - Πρόγραμμα μαθημάτων - Λίβανος; Ολυμπισμός; Ολυμπιακό κίνημα; Ολυμπιακές αξίες; Physical education and training - Study and teaching - Lebanon; Olympic education - Curriculum - Lebanon; Olympic education - Study and teaching - Lebanon; Physical education and training - Curriculum - Lebanon; Olympism; Olympic movement; Olympic values; Lebanon; Lebanese Schools; Olympic Education; Olympism; Social Cohesion